2003
DOI: 10.1063/1.1608472
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and frequency characteristics of the interfacial capacitance in thin-film barium–strontium–titanate capacitors

Abstract: Thin film Au/Ba0.5Sr0.5TiO3/SrRuO3 capacitor structures, with a thickness of dielectric varying between ∼70 and ∼950 nm, were deposited on {001} MgO single-crystal substrates using pulsed laser deposition. Low-field dielectric measurements were performed as a function of temperature and frequency. At all temperatures and frequencies, the dielectric response as a function of thickness was found to adhere reasonably well to the so-called “series capacitor model,” from which nominal “bulk” and “interfacial” capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
23
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…Experimentally, it was revealed that the inverse of the measured capacitance varies linearly with the film thickness. 1,2,[9][10][11][12][13][14][15] This observation led to a widely accepted interpretation of the experimental data in terms of a "series capacitor model." 9 According to such model, the measured capacitance density c t can be described by the relation…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, it was revealed that the inverse of the measured capacitance varies linearly with the film thickness. 1,2,[9][10][11][12][13][14][15] This observation led to a widely accepted interpretation of the experimental data in terms of a "series capacitor model." 9 According to such model, the measured capacitance density c t can be described by the relation…”
Section: Introductionmentioning
confidence: 99%
“…Respectively, both the interface capacitance and the size-driven changes in the body of the film contribute to the thickness variation of the measured permittivity, as it has been emphasized in the paper. Although the mentioned almost linear dependence d / Јϰ d can be observed in some thin-film heterostructures 5 ͑and not in others 6 ͒, it can hardly be used for determining the interface parameters.…”
mentioning
confidence: 99%
“…Thus the often observed fair linear fit of the dependence of d / Ј on thickness d ͑usually four to maximum ten experimental points͒, with the temperature dependent fitting parameters, cannot be unhesitatingly explained as originating solely from the interface capacitance. Moreover, the accompanying thickness dependence of the temperature of the dielectric maximum 5 indicates the changes in the phase diagram of thin film. Respectively, both the interface capacitance and the size-driven changes in the body of the film contribute to the thickness variation of the measured permittivity, as it has been emphasized in the paper.…”
mentioning
confidence: 99%
“…͑1͒ in temperature space-adherence has been observed at all temperatures at which it has been applied. 4 In addition, Tyunina and Levoska argue that the apparent straight line fit to data in the paraelectric state, in their CurieWeiss plots, demonstrates that there cannot be temperature dependence in any "series capacitance component." Figure 1͑a͒ below is a plot on a similar scale to those in Fig.…”
mentioning
confidence: 99%
“…On this scale, the Curie-Weiss plot looks to be linear from 340 to 400 K. However, plots of the form of Eq. ͑1͒ were previously performed on this system at a series of different temperatures 4 and showed that the value of K was actually temperature dependent. There is thus an apparent conflict.…”
mentioning
confidence: 99%